Design evaluation and performance assessment of rotorcraft technology by 2050 - Stevens, Jos; Rademaker, Edward; Scullion, Calum; Vouros, Stavros; van Oosten, Nico; Misté, Gianluigi; Venturelli, Giovanni; Nalianda, Devaiah; Pachidis, Vassilios; Benini, Ernesto (Netherlands Aerospace Centre (NLR), 2019)
The extended Clean Sky Joint Technology Initiative (JTI) within the EU Horizon 2020 Framework Programme [Ref. 1] proposes to introduce a number of concept aircraft and rotorcraft to replace reference technology counterparts at different time scales (2020/2035/2050). This Clean Sky 2 (CS2) promotes the importance of those concept configurations and their application in the future. An increasing global demand within and outside the European Union (EU) for an efficient air mobility and transportation system (i.e. more flexible, resilient, effective and affordable), and future projected growth for its application, will lead to the requirement for development of highly optimised transportation solutions.